2015
DOI: 10.1038/ncomms7047
|View full text |Cite
|
Sign up to set email alerts
|

A subcutaneous adipose tissue–liver signalling axis controls hepatic gluconeogenesis

Abstract: The search for effective treatments for obesity and its comorbidities is of prime importance. We previously identified IKK-ε and TBK1 as promising therapeutic targets for the treatment of obesity and associated insulin resistance. Here we show that acute inhibition of IKK-ε and TBK1 with amlexanox treatment increases cAMP levels in subcutaneous adipose depots of obese mice, promoting the synthesis and secretion of the cytokine IL-6 from adipocytes and preadipocytes, but not from macrophages. IL-6, in turn, sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 48 publications
11
71
1
Order By: Relevance
“…Specifically, TBK1 C-terminal coiled-coil domain, but not its kinase activity, is involved in neurodegenerative disease pathogenesis. In contrast, our study (2) clearly shows that Compound II inhibits TBK1 kinase activity without affecting total protein abundance. Thus, specific TBK1 kinase inhibitors are unlikely to directly impact its scaffolding function in the neurologic processes.…”
contrasting
confidence: 50%
“…Specifically, TBK1 C-terminal coiled-coil domain, but not its kinase activity, is involved in neurodegenerative disease pathogenesis. In contrast, our study (2) clearly shows that Compound II inhibits TBK1 kinase activity without affecting total protein abundance. Thus, specific TBK1 kinase inhibitors are unlikely to directly impact its scaffolding function in the neurologic processes.…”
contrasting
confidence: 50%
“…Administration of this selective drug to obese mice produced reversible weight loss and improved insulin sensitivity, reduced inflammation and attenuated hepatic steatosis (Reilly et al, 2013). A primary target of amlexanox in rodents is the subcutaneous fat tissue, where it increases energy expenditure partly by enhancing catecholamine sensitivity and inducing the browning of adipocytes, in the process burning energy to restore metabolic flexibility (Mowers et al, 2013; Reilly et al, 2015). The increase in catecholamine sensitivity also resulted in a transient increase in IL-6 synthesis and secretion from adipocytes and preadipocytes, which was responsible for acute lowering of blood sugar via reduced hepatic glucose output (Reilly et al, 2015).…”
mentioning
confidence: 99%
“…Because IKBKE is directly activated by activating mutation of EGFR and amlexanox is an approved small-molecule therapeutic presently used in the clinic to treat aphthous ulcers (31), and in clinical trial for obesity (32), we assumed that amlexanox could preferentially inhibit cell survival in NSCLCs with activating EGFR mutation including acquired EGFR T790M . We treated a panel of NSCLC cell lines with increasing concentrations of amlexanox and found that the EGFR mutant cell lines, including acquired-resistant lines H1975 and H1650, are more sensitive to amlexanox (GI 50 20 and 30μM) compared to the NSCLCs with wild type EGFR (GI 50 >80μM) (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we demonstrated that knockdown of IKBKE largely inhibits EGFR-driven NSCLC cell survival. In addition, amlexanox, an IKBKE inhibitor currently in clinical trial for obesity and diabetes (32), preferentially inhibits cell viability in EGFR-mutant NSCLC cell lines. While third-generation EGFR inhibitors, such as AZD9291, CO-1686 and WZ4002, are capable of inhibiting mutant EGFR with T790M, recent studies have shown that patients develop acquired resistance to these inhibitors due to new activating EGFR-C797S mutation (46, 47).…”
Section: Discussionmentioning
confidence: 99%